IDENTIFIKASI DAN STRATEGI PENGEMBANGAN UMKM HOME INDUSTRY BINAAN LPB PABANET DI SANGATTA - Siti Nur Sholikhah (Tinta Nusantara 2018 Vol.1, 2023)
The research objective to be achieved is to identify and find out the development strategy for UMKM Home Industry Assisted by LPB Pabanet. The analytical method used is the identification of areas and data analysis of UMKM assisted by LPB Pabanet. The population in this study is all Home Industry SMEs that are assisted by LPB Pabanet. The results of this study use a target setting diagram / priority scale for the empowerment and development of MSMEs to make it easier to describe data that shows the number of MSMEs that have urgent, non-urgent problems and MSMEs that have important, and very important problems.